2023
DOI: 10.3390/ijms24043301
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Lowering Activity of Vitisin A Is Mediated by Inhibiting Cholesterol Biosynthesis and Enhancing LDL Uptake in HepG2 Cells

Abstract: Pyranoanthocyanins have been reported to possess better chemical stability and bioactivities than monomeric anthocyanins in some aspects. The hypocholesterolemic activity of pyranoanthocyanins is unclear. In view of this, this study was conducted to compare the cholesterol-lowering activities of Vitisin A with the anthocyanin counterpart Cyanidin-3-O-glucoside(C3G) in HepG2 cells and to investigate the interaction of Vitisin A with the expression of genes and proteins associated with cholesterol metabolism. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…The J26P intervention increased the relative expression of LDLR in the liver compared with HCD controls, suggesting that J26P may reduce serum and liver LDL‐C levels by increasing LDLR expression. It was shown that Pyranoanthocyanins can promote intracellular LDL uptake by upregulating the expression level of LDLR in HepG2 cells, showing hypocholesterolemia activity, which is consistent with the results of the present study (Yuan et al., 2023). SREBP‐2 regulates the expression of HMGCR, the rate‐limiting enzyme in cholesterol synthesis, and LDLR‐mediated cholesterol absorption (Y. Li et al., 2017).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The J26P intervention increased the relative expression of LDLR in the liver compared with HCD controls, suggesting that J26P may reduce serum and liver LDL‐C levels by increasing LDLR expression. It was shown that Pyranoanthocyanins can promote intracellular LDL uptake by upregulating the expression level of LDLR in HepG2 cells, showing hypocholesterolemia activity, which is consistent with the results of the present study (Yuan et al., 2023). SREBP‐2 regulates the expression of HMGCR, the rate‐limiting enzyme in cholesterol synthesis, and LDLR‐mediated cholesterol absorption (Y. Li et al., 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, we further explored the effect of J26P on the expression of key proteins of liver cholesterol metabolism. HMGCR is the rate‐limiting enzyme for the de novo synthesis of cholesterol in vivo (Yuan et al., 2023). In addition, J26P does not affect the expression of liver HMGCR in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[97][98][99][100] Several studies have highlighted the role of long-chain polyunsaturated fatty acids in regulating the levels and/or expression of proteins involved in cholesterol synthesis, uptake, and transport in peripheral tissues as well as in the brain. [101][102][103][104][105][106] Preclinical studies have also noted that many flavonoids (e.g., anthocyanidins, flavanols, and flavone subclasses) influence cholesterol metabolism by regulating cellular cholesterol synthesis, 107,108 efflux, 109,110 and by inhibiting intestinal absorption. 111,112 Furthermore, in clinical studies dietary intake of flavonoids has been associated with beneficial changes in serum biomarkers related to cholesterol metabolism.…”
Section: Diet-derived Compounds and Cholesterol Metabolismmentioning
confidence: 99%
“…In our previous study, carboxylpyranocyanidin-3-O-glucoside (carboxyl-pycy-3-gluc) was successfully generated by employing the black soybean peel extracts and pyruvic acids through a 15-day reaction in a water bath. 12 The high purity of carboxyl-pycy-3-gluc was then achieved using preparative medium-pressure liquid chromatography, for which the purity is over 96%. We also demonstrated that carboxyl-pycy-3-gluc demonstrated an absence of cytotoxicity and a more effective hypocholesterolemia activity compared to Cy-3-gluc, as well as an excellent immunomodulatory effect.…”
Section: Introductionmentioning
confidence: 99%